Diagnostic value of thyrotrophin releasing hormone tests in elderly patients with atrial fibrillation. Issue 6498 (21st September 1985) - Davies, A B; Williams, I; John, R; Hall, R; Scanlon, M F
Abstract : A prospective study was carried out to compare clinical and biochemical thyroid states with responses of thyroid stimulating hormone (TSH) to thyrotrophin releasing hormone (TRH) in elderly patients with either atrial fibrillation (n = 75; mean age (SD) 79.3 (6.0) years) or sinus rhythm (n = 73; mean age 78.4 (5.6) years) admitted consecutively to the department of geriatric medicine. No patient in either group had symptoms or signs of hyperthyroidism. Overall, the TSH responses to TRH did not differ significantly between the two groups. Ten (13%) of the patients with atrial fibrillation (of whom four had raised thyroid hormone concentrations) and five (7%) of the patients with sinus rhythm showed no TSH response to TRH while 26% of each group (20 and 19 patients, respectively) showed a much reduced response. Only one of 13 patients with apparently isolated atrial fibrillation showed no TSH response to TRH, and none of these 13 patients was hyperthyroid. In particular, three patients (two with atrial fibrillation and one with sinus rhythm) who showed no TSH response to TRH at presentation exhibited a return of TSH response to TRH at follow up six weeks later. In conclusion, reduced or absent TSH responses to TRH are common in sick elderly patients whether they have atrial fibrillation or sinus rhythm and whether they are euthyroid or hyperthyroid biochemically. An absence of response is therefore an uncertain marker of hyperthyroidism in these groups of patients, and diagnosis and ablative treatment should be based at least on the presence of raised circulating free triiodothyronine or free thyroxine concentrations, or both.